An alternative route to the synthesis of lignans intermediates - Masunari, A.; Ishida, E.; Trazzi, G.; Almeida, W. P.; Coelho, F. (Marcel Dekker Inc, 2001)
The preparation of beta -hydroxylignans intermediates via Baylis-Hillman reaction is described.